Substrate Specificity and Activity Regulation of Protein Kinase MELK - Monique Beullens; Sadia Vancauwenbergh; Nick Morrice; Rita Derua; Hugo Ceulemans; Etienne Waelkens; Mathieu Bollen (2005)
Maternal embryonic leucine zipper kinase (MELK) is a protein Ser/Thr kinase that has been implicated in stem cell renewal, cell cycle progression, and pre-mRNA splicing, but its substrates and regulation are not yet known. We show here that MELK has a rather broad substrate specificity and does not appear to require a specific sequence surrounding its (auto)phosphorylation sites. We have mapped no less than 16 autophosphorylation sites including serines, threonines, and a tyrosine residue and show that the phosphorylation of Thr167 and Ser171 is required for the activation of MELK. The expression of MELK activity also requires reducing agents such as dithiothreitol or reduced glutathione. Furthermore, we show that MELK is a Ca2+-binding protein and is inhibited by physiological Ca2+ concentrations. The smallest MELK fragment that was still catalytically active comprises the N-terminal catalytic domain and the flanking ubiquitin-associated domain. A C-terminal fragment of MELK functions as an autoinhibitory domain. Our data show that the activity of MELK is regulated in a complex manner and offer new perspectives for the further elucidation of its biological function. Maternal embryonic leucine zipper kinase (MELK) is a protein Ser/Thr kinase that has been implicated in stem cell renewal, cell cycle progression, and pre-mRNA splicing, but its substrates and regulation are not yet known. We show here that MELK has a rather broad substrate specificity and does not appear to require a specific sequence surrounding its (auto)phosphorylation sites. We have mapped no less than 16 autophosphorylation sites including serines, threonines, and a tyrosine residue and show that the phosphorylation of Thr167 and Ser171 is required for the activation of MELK. The expression of MELK activity also requires reducing agents such as dithiothreitol or reduced glutathione. Furthermore, we show that MELK is a Ca2+-binding protein and is inhibited by physiological Ca2+ concentrations. The smallest MELK fragment that was still catalytically active comprises the N-terminal catalytic domain and the flanking ubiquitin-associated domain. A C-terminal fragment of MELK functions as an autoinhibitory domain. Our data show that the activity of MELK is regulated in a complex manner and offer new perspectives for the further elucidation of its biological function. The AMP-activated protein kinase (AMPK) 5The abbreviations used are: AMPKAMP-activated protein kinaseKA1kinase-associated 1 domainMBPmyelin basic proteinMELKmaternal embryonic leucine zipper kinaseNIPP1nuclear inhibitor of protein phosphatase-1UBAubiquitin-associated domainDTTdithiothreitol. is the best characterized member of the subfamily of AMPK-related protein Ser/Thr kinases (1Hardie D.G. Carling D. Carlson M. Annu. Rev. Biochem. 1998; 67: 821-855Crossref PubMed Scopus (1288) Google Scholar, 2Manning G. Whyte D.B. Martinez R. Hunter T. Sudarsanam S. Science. 2002; 298: 1912-1934Crossref PubMed Scopus (6458) Google Scholar). It is allosterically activated by AMP and controls processes that restore the energy charge in the cell. The other members of the subfamily of AMPK-related kinases include the protein kinases ARK5, BRSK, MARK, MELK, QIK, NUAK, and SNARK, which fulfill functions in processes as diverse as cell cycle progression, cell survival, cell differentiation, and microtubule stability (3Levebvre D.L. Bai Y. Shahmolky N. Sharma M. Poon R. Drucker D.J. Rosen C.F. Biochem. J. 2001; 355: 297-305Crossref PubMed Google Scholar, 4Suzuki A. Kusakai G. Kishimoto A. Lu J. Ogura T. Lavin M.F. Esumi H. J. Biol. Chem. 2003; 278: 48-53Abstract Full Text Full Text PDF PubMed Scopus (115) Google Scholar, 5Lizcano J.M. Goransson O. Toth R. Deak M. Morrice N.A. Boudeau J. Hawley S.A. Udd L. Makela T.P. Hardie D.G. Alessi D.R. EMBO J. 2004; 23: 833-843Crossref PubMed Scopus (1088) Google Scholar, 6Tassan J.-P. Le Goff X. Biol. Cell. 2004; 96: 193-199Crossref PubMed Scopus (86) Google Scholar). With the exception of maternal embryonic leucine zipper kinase (MELK), which is activated by autophosphorylation, the AMPK-related kinases are activated through phosphorylation of their T-loop by protein kinase LKB1 (5Lizcano J.M. Goransson O. Toth R. Deak M. Morrice N.A. Boudeau J. Hawley S.A. Udd L. Makela T.P. Hardie D.G. Alessi D.R. EMBO J. 2004; 23: 833-843Crossref PubMed Scopus (1088) Google Scholar, 7Woods A. Johnstone S.R. Dickerson K. Leiper F.C. Fryer L.G.D. Neumann D. Schlattner U. Wallimann T. Carlson M. Carling D. Curr. Biol. 2003; 13: 2004-2008Abstract Full Text Full Text PDF PubMed Scopus (1371) Google Scholar) and the calcium- and calmodulin-dependent protein kinase II (8Hurley R.L. Anderson K.A. Franzone J.M. Kemp B.E. Means A.R. Witters L.A. J. Biol. Chem. 2005; 280: 29060-29066Abstract Full Text Full Text PDF PubMed Scopus (834) Google Scholar). AMP-activated protein kinase kinase-associated 1 domain myelin basic protein maternal embryonic leucine zipper kinase nuclear inhibitor of protein phosphatase-1 ubiquitin-associated domain dithiothreitol. The catalytic domain of the AMPK-related protein kinases is located in the N terminus of their catalytic subunit. Some of the AMPK-related protein kinases, including MELK, have an ubiquitin-associated (UBA) domain adjacent to the catalytic domain and a C-terminal kinase-associated 1 (KA1) domain. The function of the latter domains are poorly understood. UBA domains are known to bind (poly)ubiquitin and have been suggested to thereby prevent additional ubiquitination and proteosomal degradation of the target protein (9Buchberger A. Trends Cell Biol. 2002; 12: 216-221Abstract Full Text Full Text PDF PubMed Scopus (151) Google Scholar, 10Hartmann-Petersen R. Semple C.A.M. Ponting C.P. Hendil K.B. Gordon C. Int. J. Biochem. Cell Biol. 2003; 35: 629-636Crossref PubMed Scopus (28) Google Scholar, 11Mueller T.D. Kamionka M. Feigon J. J. Biol. Chem. 2004; 279: 11926-11936Abstract Full Text Full Text PDF PubMed Scopus (90) Google Scholar, 12Davies G.C. Ettenberg S.A. Coats A.O. Mussante M. Ravichandran S. Collins J. Nau M.M. Lipkowitz S. Oncogene. 2004; 23: 7104-7115Crossref PubMed Scopus (73) Google Scholar). In some proteins, UBA domains appear to function as dimerization domains (13Bertolaet B.L. Clarke D.J. Wolff M. Watson M.H. Henze M. Divita G. Reed S.I. J. Mol. Biol. 2001; 313: 955-963Crossref PubMed Scopus (102) Google Scholar). Between the UBA and the KA1 domains, MELK contains a TP dipeptide-rich domain that is phosphorylated in mitotically arrested cells and mediates binding to the transcription and splicing factor NIPP1 (14Vulsteke V. Beullens M. Boudrez A. Keppens S. Van Eynde A. Rider M.H. Stalmans W. Bollen M. J. Biol. Chem. 2004; 279: 8642-8647Abstract Full Text Full Text PDF PubMed Scopus (73) Google Scholar). Preliminary evidence implicates MELK in various cellular processes. MELK binds tightly to the zinc finger-like protein ZPR9 and causes its nuclear accumulation (15Seong H.-A. Gil M. Kim K.-T. Ha H. Biochem. J. 2002; 361: 597-604Crossref PubMed Google Scholar, 16Seong H.-A. Kim K.-T. Ha H. J. Biol. Chem. 2003; 278: 9655-9662Abstract Full Text Full Text PDF PubMed Scopus (36) Google Scholar). In the nucleus, ZPR9 itself interacts with the transcription factor B-Myb, a regulator of cell proliferation and differentiation, and enhances its transcriptional activity. Another interactor of MELK is the transcription and splicing factor NIPP1, but the binding of NIPP1 requires the phosphorylation of MELK on a specific threonine in its TP dipeptide-rich domain (14Vulsteke V. Beullens M. Boudrez A. Keppens S. Van Eynde A. Rider M.H. Stalmans W. Bollen M. J. Biol. Chem. 2004; 279: 8642-8647Abstract Full Text Full Text PDF PubMed Scopus (73) Google Scholar). Because wild-type MELK, but not a NIPP1-binding mutant, is a potent inhibitor of pre-mRNA splicing in nuclear extracts and because the MELK-NIPP1 interaction is increased during mitosis, it has been proposed that MELK contributes to the ending of pre-mRNA splicing just before mitosis (14Vulsteke V. Beullens M. Boudrez A. Keppens S. Van Eynde A. Rider M.H. Stalmans W. Bollen M. J. Biol. Chem. 2004; 279: 8642-8647Abstract Full Text Full Text PDF PubMed Scopus (73) Google Scholar). A third protein ligand of MELK is Cdc25B, a protein-tyrosine phosphatase that triggers mitosis by the activation of protein kinase Cdk1. Davezac et al. (17Davezac N. Baldin V. Blot J. Ducommun B. Tassan J.-P. Oncogene. 2002; 21: 7630-7641Crossref PubMed Scopus (88) Google Scholar) reported that the ectopic expression of MELK induces an accumulation of cells in G2 and that this effect was counteracted by the overexpression of Cdc25B. Intriguingly, MELK is expressed at high levels in both embryonic (18Heyer B.S. Warsowe J. Solter D. Knowles B.B. Ackerman S.L. Mol. Reprod. Dev. 1997; 47: 148-156Crossref PubMed Google Scholar, 19Heyer B.S. Kochanowski H. Solter D. Dev. Dyn. 1999; 215: 344-351Crossref PubMed Scopus (48) Google Scholar) and neural stem cells (20Geschwind D.H. Ou J. Easterday M.C. Dougherty J.D. Jackson R.L. Chen Z. Antoine H. Terskikh A. Weissman I.L. Nelson S.F. Kornblum H.I. Neuron. 2001; 29: 325-339Abstract Full Text Full Text PDF PubMed Scopus (213) Google Scholar, 21Easterday M.C. Dougherty J.D. Jackson R.L. Ou J. Nakano I. Paucar A.A. Roobini B. Dianati M. Irvin D.K. Weissman I.L. Terskikh A.V. Geschwind D.H. Kornblum H.I. Dev. Biol. 2003; 264: 309-322Crossref PubMed Scopus (56) Google Scholar), indicating that it may also play a role in stem cell functions of multipotency and self-renewal. Finally, MELK possibly contributes to oncogenesis because its expression is increased in tumor-derived progenitor cells (22Hemmati H.D. Nakano I. Lazareff J.A. Masterman-Smith M. Geschwind D.H. Bronner-Fraser M. Kornblum H.I. Proc. Natl. Acad. Sci. U. S. A. 2003; 100: 15178-15183Crossref PubMed Scopus (1555) Google Scholar) and in cancers of nondifferentiated cells (23Rhodes D.R. Yu J. Shanker K. Deshpande N. Varambally R. Ghosh D. Barette T. Pandey A. Chinnaiyan A.M. Proc. Natl. Acad. Sci. U. S. A. 2004; 101: 9309-9314Crossref PubMed Scopus (819) Google Scholar). The MELK ligands ZPR9 (15Seong H.-A. Gil M. Kim K.-T. Ha H. Biochem. J. 2002; 361: 597-604Crossref PubMed Google Scholar), NIPP1, 6M. Beullens, V. Vulsteke, S. Vancauwenbergh, and M. Bollen, unpublished data. and Cdc25B (17Davezac N. Baldin V. Blot J. Ducommun B. Tassan J.-P. Oncogene. 2002; 21: 7630-7641Crossref PubMed Scopus (88) Google Scholar) are also MELK substrates, but the significance of their phosphorylation is not clear. A major limitation in studying the role of MELK as a protein kinase is that it is not known what controls its activity and that MELK expressed in mammalian cells seems to be inactive (5Lizcano J.M. Goransson O. Toth R. Deak M. Morrice N.A. Boudeau J. Hawley S.A. Udd L. Makela T.P. Hardie D.G. Alessi D.R. EMBO J. 2004; 23: 833-843Crossref PubMed Scopus (1088) Google Scholar). This has prompted us to examine what determines the activity and substrate specificity of MELK, expressed in either bacteria or mammalian cells. We show here that MELK has a rather broad substrate specificity and that its activity is complexly regulated by autophosphorylation, autoinhibition, Ca2+ ions, and reducing agents. Materials—Mouse monoclonal anti-FLAG antibodies were obtained from Stratagene. Anti-phosphothreonine antibodies were obtained from Zymogen, and anti-phosphotyrosine antibodies were from Santa Cruz Biotechnology. Reduced and oxidized glutathione and PHOS-Select™ gel were purchased from Sigma. 45CaCl2 (2.2 mCi/ml, 134 μg of Ca2+/ml) was obtained from Amersham Biosciences. Preparation of Recombinant MELK (Mutants)—Wild-type MELK and the indicated MELK mutants and fragments were cloned in the pET16b vector, in-frame with the polyhistidine tag. The His-tagged proteins were purified on Ni2+-Sepharose™6 Fast Flow (Amersham Biosciences). The constructs encoding FLAG-tagged MELK (fragments) have been described previously (14Vulsteke V. Beullens M. Boudrez A. Keppens S. Van Eynde A. Rider M.H. Stalmans W. Bollen M. J. Biol. Chem. 2004; 279: 8642-8647Abstract Full Text Full Text PDF PubMed Scopus (73) Google Scholar). Point mutations were made according to the QuikChange site-directed mutagenesis protocol of Stratagene, using the appropriate primers and templates. The sequences of the DNA constructs were verified by DNA sequencing. Cell Cultures and Immunoprecipitations—COS-1 and HEK293T cells were grown in Dulbecco's modified Eagle's medium supplemented with 10% (v/v) fetal calf serum. 48 h after transfection, the cells were washed twice with ice-cold phosphate-buffered saline and lysed in 50 mm Tris at pH 7.5, 0.3 m NaCl, 0.5% (v/v) Triton X-100, 0.5 mm phenylmethanesulfonyl fluoride, 0.5 mm benzamidine, and 5 μm leupeptin. After sonication, the cell lysates were cleared by centrifugation (10 min at 10,000 × g), and the supernatants were used for immunoprecipitations. The cleared cell lysates were incubated with anti-FLAG antibodies coupled to protein G-Sepharose (Amersham Biosciences) for 3 h at 10 °C. After one wash with Tris-buffered saline supplemented with 0.2 m LiCl and three washes with Tris-buffered saline plus 0.1% (v/v) Nonidet P-40, the beads were resuspended in 25 mm Tris at pH 7.5 and used for kinase assays and immunoblotting with anti-FLAG antibodies. Protein Kinase Assays—The kinase activities of MELK (mutants) and fragments were determined with the indicated substrates for 1 h at 30 °C in a buffer containing 25 mm Tris at pH 7.5, 0.1 mm [γ-32P]ATP, and 2 mm magnesium acetate. Reactions with peptide substrates were stopped by transfer of the assay mixture to P81 papers and washing with 75 mm orthophosphoric acid. Reactions with myelin basic protein (MBP) as substrate were run on SDS-PAGE and analyzed by autoradiography. Peptide Chip—The Trial PepChip kinase array (Pepscan Systems B.V.) contains 2 × 192 peptides, divided in 2 × 4 subarrays of 6 × 4 spots. The incubation was done as described in the manual. Briefly, the PepChip kinase slide was incubated for 2 h at 30°C in the following reaction mixture: 50 mm Hepes at pH 7.4, 20 mm MgCl2, 0.02 mg/ml bovine serum albumin, 0.01% Brij-35, 20 mm DTT, 10 μm [γ-33P]ATP, and 0.5 μm MELK. After the incubation, the chip was washed once with phosphate-buffered saline supplemented with 1% (v/v) Triton X-100, washed twice with 2 m NaCl plus 1% (v/v) Triton X-100 and then rinsed twice with Milli Q water before drying. The dry PepChip kinase array was analyzed on a phosphorimaging device (Storm 640; Molecular Dynamics). 45Ca2+ Overlay and Ca2+ Buffer—The indicated amounts of MELK or NIPP1 were spotted on a polyvinylidene difluoride membrane (Hybond-P; Amersham Biosciences), and the 45Ca2+ binding was carried out as described previously (24Sienaert I. Missiaen L. De Smedt H. Parys J.B. Sipma H. Casteels R. J. Biol. Chem. 1997; 272: 25899-25906Abstract Full Text Full Text PDF PubMed Scopus (122) Google Scholar). The free Ca2+ concentration in bath solutions was calculated with the CaBuf program (Droogmans G., KULeuven), taking into consideration the values of pH, temperature, ionic strength, association constants, and Mg2+ concentration. Mapping of Autophosphorylation Sites of MELK—Phospho-amino acid analysis by thin-layer chromatography was done as described previously (25Beullens M. Van Eynde A. Bollen M. Stalmans W. J. Biol. Chem. 1993; 268: 13172-13177Abstract Full Text PDF PubMed Google Scholar). MELK-(1-340) was incubated for 3 h at 30 °C in a buffer containing 25 mm Tris at pH 7.5, 0.1 mm [γ-32P]ATP, and 2 mm magnesium acetate to allow complete autophosphorylation. The autophosphorylation sites of 32P-labeled MELK-(1-340) were determined by phosphopeptide sequencing as well as by mass spectrometry. For this purpose, 32P-labeled MELK-(1-340) was first subjected to a reduction for 45 min at 60 °C with 10 mm DTT and then to an alkylation for 45 min at room temperature in the dark with 35 mm iodoacetamide. The remaining iodoacetamide was neutralized by an incubation with 15 mm DTT for 45 min at room temperature in the dark. Subsequently, the proteins were precipitated with 10% trichloroacetic acid, and the aceton-washed pellet was digested overnight with 5 μg/μl trypsin in 200 mm ammonium bicarbonate plus 0.1% RapiGest (Waters). The resulting peptides were separated on a μRPC C2/C18 SC2.1/10 column (SMART System; Amersham Biosciences), equilibrated in 0.1% trifluoroacetic acid, and eluted with a linear gradient of 0-70% acetonitrile in 0.1% trifluoroacetic acid. The radioactive fractions were either analyzed by a 492 Procise (Applied Biosystems) amino acid sequencer, operated in the pulsed liquid mode, or by electrospray mass spectrometry on an Applied Biosystems API 3000 tandem mass spectrometer. The latter was equipped with a Protana nanospray source. Identification of the phosphopeptides and determination of the phosphorylation sites were performed using the neutral loss scan mode and the product ion scan mode, respectively. The autophosphorylation sites of full-length MELK-(1-651) were also determined by mass spectrometry, using a different protocol. Wild-type MELK was digested in-gel with trypsin (5 μg/ml) in ammonium bicarbonate plus 0.1% N-octyl-glucoside as described previously (5Lizcano J.M. Goransson O. Toth R. Deak M. Morrice N.A. Boudeau J. Hawley S.A. Udd L. Makela T.P. Hardie D.G. Alessi D.R. EMBO J. 2004; 23: 833-843Crossref PubMed Scopus (1088) Google Scholar). Digests were diluted to 0.1 ml with PHOS-Select™ wash/bind buffer (0.25 m acetic acid, 30% acetonitrile) and supplemented with 30 μl of a 10% (v/v) PHOS-Select™ gel, equilibrated in the wash/bind buffer. After an incubation for 20 min, the beads were captured in an Eppendorf gel loader tip to form a mini-column. The beads were washed three times with 30 μl wash/bind buffer and eluted with two times 25 μlof0.4 m ammonium hydroxide. The eluate was dried under vacuum and resuspended in 5% formic acid for analysis by matrix-assisted laser desorption ionization time-of-flight mass spectrometry on an Applied Biosystems 4700 Proteomics Analyser using α-cyano-4-hydroxy cinnamic acid (5 mg/ml + 10 mm ammonium phosphate in 50% acetonitrile, 0.1% trifluoroacetic acid) as matrix. Electrospray liquid chromatography-mass spectrometry was performed on a Dionex Ultimate capillary high pressure liquid chromatography system coupled to an Applied Biosystems 4000 Q TRAP mass spectrometer. The peptides were separated on a PepMap C18 column equilibrated in 0.1% formic acid/water and developed with a discontinuous acetonitrile gradient at 350 μl/min. MELK Has a Broad Substrate Specificity—Consistent with a previous report by Lizcano et al. (5Lizcano J.M. Goransson O. Toth R. Deak M. Morrice N.A. Boudeau J. Hawley S.A. Udd L. Makela T.P. Hardie D.G. Alessi D.R. EMBO J. 2004; 23: 833-843Crossref PubMed Scopus (1088) Google Scholar), bacterially expressed human MELK was spontaneously active and phosphorylated the AMARA peptide, a classical substrate of the subfamily of AMPK-related protein kinases (Fig. 1A). Another widely used substrate for these kinases, the SAMS peptide, was an even better in vitro substrate of MELK. Surprisingly, MELK also phosphorylated a broad range of structurally unrelated proteins, such as MBP, Histone H1, and the splicing factors CDC5L, NIPP1, and SAP155 (not shown). To obtain some insights into the substrate determinants of MELK, we screened a peptide chip for candidate substrates (Fig. 1B). The used chip contained two identical sets of 192 peptides that all comprise established in vivo phosphorylation sites. Numerous peptides on this chip were phosphorylated by MELK. The three best MELK substrates were peptides derived from casein, eukaryotic initiation factor 2α, and lamin B1. These peptides did not show any structural similarity and were also very different from the AMARA and SAMS peptides (Fig. 1C) and from the sequences surrounding the established MELK phosphorylation sites of ZPR9, CDC25B, and NIPP1 (not shown). Using phospho-epitope-specific antibodies, we have confirmed that Ser51 of full-length, recombinant eukaryotic initiation factor 2α is phosphorylated by MELK (not shown). Collectively, our data indicate that MELK has a rather broad substrate specificity in vitro. MELK Contains an Autoinhibitory Domain—The catalytic domain of MELK is located in its N terminus. The C-terminal 60% of MELK comprises consecutively a UBA domain, a TP dipeptide-rich domain, and a KA1 domain (Fig. 2A). To examine whether the latter domains affect the catalytic activity of MELK, we generated various MELK mutants (Fig. 2B). Deletion of the KA1 domain or the KA1 plus TP-rich domains increased the Kcat/Km ratio 2-4-fold, using either the SAMS peptide or MBP as substrates (Fig. 2C). However, the additional deletion of the UBA domain, as in MELK-(1-266), resulted in an inactive enzyme, indicating that the UBA domain is essential for the expression of catalytic activity. Consistent with this notion, we found that the deletion of the UBA domain from full-length MELK also resulted in an inactive kinase. Likewise, MELK was completely inactive following the fortuitous mutation of the three first residues (D283K/D284K/D285K) of the UBA domain. Our observation that the N-terminal half of MELK is more active than the full-length protein (Fig. 2) suggested that the C-terminal half of MELK functions as an autoinhibitory domain. Accordingly, we found that the catalytic activity of full-length MELK (not shown) or MELK-(1-340) was inhibited by the addition of MELK-(326-651) (Fig. 3A). With MBP as substrate, a nearly complete inhibition was obtained with 15 μm MELK-(326-651) (Fig. 3A). Using smaller MELK fragments, we could delineate an inhibitory fragment to residues 326-530, which largely corresponds to the TP-rich domain (Fig. 2A). MELK-(602-651), essentially comprising the KA1 domain, was not inhibitory. The latter finding was unexpected because the deletion of the KA1 domain increased the catalytic efficiency of MELK (Fig. 2C). Lineweaver-Burk plots showed that the inhibition of MELK-(1-340) by MELK-(326-601) was largely accounted for by a decreased Vmax (Fig. 3B), consistent with the increased Kcat for MELK-(1-340) as compared with the Kcat of wild-type MELK (Fig. 2C). The inhibition of MELK-(1-340) by MELK-(326-651), MELK-(326-601), and MELK-(326-530) was also detected when the SAMS peptide was used as substrate, but the maximal extent of inhibition was less pronounced with this substrate and amounted to only about 65% (not shown). Autophosphorylation of MELK—Using immunoblotting with phospho-epitope-specific antibodies and phospho-amino acid analysis by thin-layer chromatography, we found that bacterially expressed MELK was phosphorylated on serine, threonine, and tyrosine residues and that the level of phosphorylation was further augmented by incubation of the purified enzyme with MgATP (not shown). The phosphorylation on Ser and Thr could be reversed by incubation with the catalytic subunit of protein phosphatase-1, whereas the phosphorylation on tyrosine was reversed by incubation with a protein-tyrosine phosphatase from Yersinia enterocolitica (not shown). The phosphorylation of MELK is likely to be an autocatalytic process because the inactive variant MELK-D150A (14Vulsteke V. Beullens M. Boudrez A. Keppens S. Van Eynde A. Rider M.H. Stalmans W. Bollen M. J. Biol. Chem. 2004; 279: 8642-8647Abstract Full Text Full Text PDF PubMed Scopus (73) Google Scholar), which is mutated in the essential DFG triplet of kinase subdomain VII, was not phosphorylated at all. We have initially used mass spectrometry to map the autophosphorylation sites of bacterially expressed wild-type MELK and MELK-(1-340). This resulted in the identification of 14 autophosphorylation sites, distributed all over the polypeptide chain, with the exclusion of the UBA and KA1 domains (TABLE ONE). Surprisingly, two independent mass spectrometric analyses did not identify tyrosine-phosphorylated peptides, which was in contrast with the data of immunoblot analysis. Because MELK contains a tyrosine in its catalytic loop (Tyr163) that is not conserved in the catalytic loop of the other members of the subfamily of AMPK-activated protein kinases (Fig. 4A) and because MELK is also the only member of this subfamily that is known to be autophosphorylated on tyrosine, we have examined whether it is perhaps Tyr163 that is autophosphorylated by MELK. In accordance with this view, we found that the autophosphorylation on tyrosine was largely lost in MELK-Y163F, despite the fact that this mutant was still catalytically active toward an exogenous substrate (Fig. 4B). We have also used N-terminal sequencing by Edman degradation to map autophosphorylation sites in the catalytic loop. A tryptic peptide that was derived from 32P-labeled MELK-(1-340), was phosphorylated on both Thr167 and Ser171 (not shown). The latter site was not identified by mass spectrometry, possibly because Ser171 was phosphorylated substoichiometrically (see "Discussion"). In conclusion, the total number of autophosphorylation sites that we mapped amounted to 16 (Fig. 4C).TABLE ONEMapping of autophosphorylation sites by mass spectrometryPhosphopeptideResiduesMassPhosphorylated residueIKpTEIEALK54–621123.6Thr56IKpTEIEALKNLR54–651508.4Thr56DYHLQpTCCGSLAYAAPELIQGK162–1832670.2Thr167GNKDYHLQpTCCGSLAYAAPELIQGK159–1832969.5Thr167RIpSMK251–255713.6Ser253KRIpSMK250–255841.6Ser253LSpSFSCGQASATPFTDIK334–3512043.9Ser336LSpSFSCGQApSATPFTDIK334–3512123.9Ser336, Ser343NNWpSLEDVTASDK352–3651644.7Ser355TpSQFTKYWpTESNGVESK390–4062150.9Ser391, Thr398YWpTESNGVESK396–4061378.6Thr398pSLTPALCR407–4141044.5Ser407pSAVKNEEYFMFPEPK431–4451894.9Ser431LMpTGVISPER492–5011181.6Thr494CRpSVELDLNQAHMEETPK503–5202284.0Ser505VFGpSLER526–532886.4Ser529GLDKVIpTVLTR533–5431293.7Thr539 Open table in a new tab MELK did not phosphorylate the SAMS peptide when the phosphorylatable residue (Ser79) was replaced by a tyrosine (not shown), indicating that MELK is not a true dual specificity protein kinase and can only phosphorylate tyrosine(s) autocatalytically. Also, the autophosphorylation rate of MELK was independent of its dilution (not shown), suggesting that the autophosphorylation represents an intramolecular rather than an intermolecular process. In further agreement with this view, we found that wild-type MELK neither phosphorylated the recombinant (inactive) catalytic domain of MELK nor a synthetic peptide (residues 159-173) comprising the catalytic loop of MELK and including the autophosphorylation sites Tyr163, Thr167, and Ser171 (not shown). We have subsequently explored the role of autophosphorylation of the catalytic domain of MELK by site-directed mutagenesis (Fig. 5). MELK-(1-340)-T167A was inactive, strongly suggesting that autophosphorylation on this site is essential for activity. However, MELK-(1-340)-T167D was active, indicating that this replacement mimicked the phosphorylation of Thr167. Interestingly, both MELK-(1-340)-S171A and MELK-(1-340)-S171D were inactive, suggesting that phosphorylation of Ser171 is essential for activity but is not mimicked by an acidic residue. Mutation of Thr56 or Ser253 into either an aspartic acid or an alanine did not measurably affect the activity of MELK-(1-340). Mutation of Tyr163 into either a phenylalanine or an aspartic acid residue also had no effect on the activity of MELK-(1-340). The Expression of MELK Activity Requires Reducing Agents—The ability of MELK to autophosphorylate and to phosphorylate an exogenous substrate was completely dependent on the presence of reducing agents (Fig. 6A). A maximal stimulation of the protein kinase activity was obtained with 5-10 mm DTT. GSH was a less potent activator than was DTT, and GSSG did not activate MELK at all. The requirement for reducing agents suggested that MELK is inactivated by the covalent modification of one or several cysteines. The involved cysteine(s) are at least partially located in the catalytic and/or UBA domains because MELK-(1-340) was also fully DTT-dependent (Fig. 6B). Accordingly, the combined mutation of all nine cysteines yielded a MELK-(1-340) variant that no longer required reducing agents to be active (Fig. 6B). However, MELK remained DTT-dependent following the separate mutation (C29V, C70V, C89A, C154A, C168A, C169A, C204A, C286A, or C339A) of each of the nine cysteines that are present in the catalytic and UBA domains (not shown), indicating that MELK-(1-340) contains at least two cysteines that can be modified and thereby cause a complete inactivation of the kinase. Gel filtration chromatography revealed that MELK is a monomer, both in the absence and presence of DTT, indicating that its activation by reducing agents is not the result of the disruption of one or more interchain disulfide bonds (not illustrated). MELK Is Inhibited by the Binding of Ca2+—Following the serendipitous observation that MELK was more active in the presence of the Ca2+ chelator EGTA, we have explored whether the activity of MELK is perhaps controlled by Ca2+. Using a Ca2+-EGTA buffer to generate various concentrations of free Ca2+, we found that the kinase activities of MELK-(1-651) and MELK-(1-340) were inhibited in a dose-dependent manner by Ca2+. Using MBP as substrate, we detected a nearly complete inhibition at free Ca2+ concentrations of around 1 μm (Fig. 7A). This roughly corresponds to the Ca2+ concentration that is detected following the stimulation of cells with a maximally effective concentration of a Ca2+ agonist. Interestingly, higher Ca2+ concentrations were somewhat less inhibitory. We obtained similar data with the SAMS peptide as kinase substrate, except that the maximal inhibition, at 1 μm Ca2+, amounted to only around 65% (not illustrated). Also, supraphysiological free Ca2+ concent